Endophytic Fungi Associated with Twigs of Buddleja asiatica Lour - Chhetri, B.K.; Maharjan, S.; Budhathoki, U. (Kathmandu University Journal of Science, Engineering and Technology, 2013)
Endophytic fungi were studied in twigs of Buddleja asiatica at two sites within Kathmandu city, Nepal. Sterile mycelia and five fertile taxa (Alternaria, Fusarium, Epicoccum, Phoma, and Cladosporium) were isolated. Alternaria, Fusarium, and sterile mycelia were isolated from both sites, whereas Epicoccum, Phoma, and Cladosporium were site-specific. Colonization frequency, isolation frequency, and diversity of fungi were higher at Site II compared to Site I.